Plasmonic enhancement of aqueous processed organic photovoltaics. Issue 31 (25th May 2021) - Chowdhury, R.; Tegg, L.; Keast, V. J.; Holmes, N. P.; Cooling, N. A.; Vaughan, B.; Nicolaidis, N. C.; Belcher, W. J.; Dastoor, P. C.; Zhou, X.
Abstract : Plasmonic Na x WO3 nanoparticles were introduced to aqueous processed organic photovoltaics with 35% device enhancement. Abstract : Sodium tungsten bronze (Na x WO3 ) is a promising alternative plasmonic material to nanoparticulate gold due to its strong plasmonic resonances in both the visible and near-infrared (NIR) regions. Additional benefits include its simple production either as a bulk or a nanoparticle material at a relatively low cost. In this work, plasmonic Na x WO3 nanoparticles were introduced and mixed into the nanoparticulate zinc oxide electron transport layer of a water processed poly(3-hexylthiophene):phenyl-C61 -butyric acid methyl ester (P3HT:PC61 BM) nanoparticle (NP) based organic photovoltaic device (NP-OPV). The power conversion efficiency of NP-OPV devices with Na x WO3 NPs added was found to improve by around 35% compared to the control devices, attributed to improved light absorption, resulting in an enhanced short circuit current and fill factor.